Stress and Relaxation Among Aging Catholic Priests. Issue 1 (2nd January 2017) - Kane, Michael N.
ABSTRACT: Using semistructured interviews, this study considered how currently active priests (n = 18) perceived physical and cognitive changes of aging, stress in their lives, and self-care. Half summarized their ministry by choosing the statement, "I'm satisfied with my life, but sometimes the days are too long." Most respondents found there were energy limitations with aging and reported health concerns that did not significantly limit pastoral activities. All were conscious of healthy self-care (diet, exercise, and medical care). Stress for most respondents came from pastoral demands of parishioners and hierarchs, their own demands for meeting the needs of all, and loneliness.